PRICE ANDVOLUME EFFECTS ASSOCIATED WITH CHANGES IN THE LQ 45 INDEX AND THE MSCI EQUITY INDEX LISTS - Harijono, A. (Gadjah Mada International Journal of Business, 2003)
This paper examines price and trading volume behavior surrounding announcements of changes in the composition of the liquidity (LQ) 45 and the Morgan Stanley Capital International (MSCI) Equity Index at the Jakarta Stock Exchange. Unlike listing studies in the developed markets, the announcements of the LQ45 Index changes have no impact on share price and trading volume. This may be due to the small role of Indonesian domestic institutional investors and purely rule-based characteristics of the LQ45 Index. On the contrary, the markets do respond to the changes in Indonesian stocks composition of the MSCI Equity Index. It seems that global portfolio managers, who dominate trading at the Jakarta Stock Exchange, rebalanced their portfolio when the changes in the MSCI Equity Index occurred because their performances are generally benchmarks to the return on the Index.